High-quality Porous Cobalt Monoxide Nanowires @ Ultrathin Manganese dioxide Sheets Core-Shell Nanowire Arrays on Ni Foam for High-Performance Supercapacitor. (10th March 2016) - Wang, Xuezhao; Xiao, Yuanhua; Su, Dangcheng; Zhou, Liming; Wu, Shide; Han, Lifeng; Fang, Shaoming; Cao, Shaokui
Abstract: A new core-shell nanostructure of CoO@MnO2 nanowire@nanosheetarrays(NNSs) was designed and directly grown on a 3D nickel foam by a simple two step solution method combined with a post annealing treatment in Ar gas. The MnO2 nanosheets can grow directly on the CoO precuor nanowires without any pretreatment, and its thickness on the CoO nanowire arrays (NAs) can also be tailored by easily adjusting the second step hydrothermal time. When acting as a electrochemical supercapacitor, the CoO@MnO2 NNAs delivers a highly enhanced specific capacitance of 3.03 F cm −2 (about 1515 F g −1 ) with a wide potential window of 0.8 V at 2.0 mA cm −2, which is superior to most reported Co3 O4 based core-shell NNAs supercapacitive electrodes. An asymmetric supercapacitor devices based on these CoO@MnO2 NNAs and aqueous electrolyte showed with a high-energy density of 0.37 mWh cm −2 at a power density of 1.7 mW cm −2, a high power density of 34.4 mW cm −2  at 0.20 mWh cm −2 and a long-term cycling ability, implying its great potential application in high-performance electrochemical supercapacitor.